Sanitizer ultraviolet box / Syed Muhammad Rohaizat Syed Muhammad Apindi … [et al.] - Syed Muhammad Apindi, Syed Muhammad Rohaizat; Azhar, Muhammad Aiman Irfan; Rozelan, Muhammad Aiman; Azmi, Muhammad Iqbal; Jamil, Muhammad Fairuz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Ultraviolet box sanitizer or known as SUV box is a new product technology according to the invasion today. This technology has been designed according to the development of ideas and creativity based on technologies available in modern times. This product was created after the occurrence of Covid-19 and during this pandemic the whole world needs a bacterial or viral exterminator such as Covid-19. Covid-19 sanitizer liquid is used to physically eradicate the corona virus such as the human body and the environment. But this liquid should not be used directly on technology such as gadgets as it will cause damage. Therefore, we have studied and argued that there are also other methods to eradicate corona virus without using liquids such as sanitizers. We have found that ultraviolet radiation is also able to kill bacteria and viruses by 99% according to scientific studies. Therefore, we have created a product that uses ultraviolet radiation technology that works to eradicate viruses or bacteria found on gadgets.